Short-Term Caloric Restriction and Subsequent Re-Feeding Compromise Liver Health and Associated Lipid Mediator Signaling in Aged Mice - Schädel, Patrick; Wichmann-Costaganna, Mareike; Czapka, Anna; Gebert, Nadja; Ori, Alessandro; Werz, Oliver (Nutrients, 2023)
Aging is characterized by alterations in the inflammatory microenvironment, which is tightly regulated by a complex network of inflammatory mediators. Excessive calorie consumption contributes to age- and lifestyle-associated diseases like obesity, type 2 diabetes, cardiovascular disorders, and cancer, while limited nutrient availability may lead to systemic health-promoting adaptations. Geroprotective effects of short-term caloric restriction (CR) can beneficially regulate innate immune receptors and interferon signaling in the liver of aged mice, but how CR impacts the hepatic release of immunomodulatory mediators like cytokines and lipid mediators (LM) is elusive. Here, we investigated the impact of aging on the inflammatory microenvironment in the liver and its linkage to calorie consumption. The livers of female young and aged C57BL/6JRj mice, as well as of aged mice after caloric restriction (CR) up to 28 days, with and without subsequent re-feeding (2 days), were evaluated. Surprisingly, despite differences in the hepatic proteome of young and old mice, aging did not promote a pro-inflammatory environment in the liver, but it reduced lipoxygenase-mediated formation of LM from polyunsaturated fatty acids without affecting the expression of the involved lipoxygenases and related oxygenases. Moreover, CR failed to ameliorate the secretion of pro-inflammatory cytokines but shifted the LM production to the formation of monohydroxylated LM with inflammation-resolving features. Unexpectedly, re-feeding after CR even further decreased the inflammatory response as LM species were markedly downregulated. Our findings raise the question of how short-term CR is indeed beneficial as a nutritional intervention for healthy elderly subjects and further stress the necessity to address tissue-specific inflammatory states.